METHODS OF PARALITURGICAL CHORAL COMPOSITIONS IN STUDENT CHOIR CLASSES - Kyfenko , Anna; Holian, Khrystyna (The Modern Higher Education Review, 2022)
The article focuses on revealing the methodology methods of paraliturgical choral compositions in student choir classes, namely, phonetic features of Church Slavonic hymns, nature of sound production, dynamic ensemble, vocal and timbre ensemble, and phrasing. The role of religious and spiritual culture, spiritual choral art is highlighted. The importance of spiritual choral music in the repertoire of the student choir is substantiated, and the system of Christian values is singled out. It was determined that currently, one of the urgent issues of art education is the revival of the spirituality of the nation, the search for new landmarks, a new system of values. The positive effect of spiritual singing on a person has been proven as well. It was determined that paraliturgical chants have a pedagogical and psychotherapeutic effect on the formation of personality, occupy an important place in the repertoire of student choirs. The interdisciplinary connections between the study of paraliturgical choral works and the subjects of the musical cycle are analysed, e.g., history of music, solfeggio, harmony, voice production, conducting. It was emphasized that in working on paraliturgical choral works, it is important for leaders of educational choral groups to master the special skills and abilities. Choral singing is a carrier of enormous informational and educational potential, containing interdisciplinary communicative connections of the main subjects of the musical cycle: solfeggio, music theory, harmony, polyphony, history of music, analysis of musical forms, solo singing, conducting. The article examines the main problem in the work of choirmasters, namely, the lack of knowledge of the traditional style of sacred music, its genre affiliation, and stylistic features.